2006
DOI: 10.1080/14734220601009606
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral alterations in an adolescent following posterior fossa tumor resection

Abstract: The posterior fossa syndrome (PFS) consists of a variety of symptoms, including cerebellar mutism, behavioral disturbances and personality changes. We report longitudinal clinical, neuroradiological and neurobehavioral findings in a 19-year-old left-handed patient, diagnosed with attentional deficit hyperactivity disorder (ADHD) at the age of 12, who underwent posterior fossa tumor resection. Although the patient did not develop cerebellar mutism after surgery, marked apathy and emotional indifference, urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Some functional magnetic resonance imaging (MRI) studies revealed the cerebello-cortical pathway with multiple fiber tracts that terminate within the regions of the contralateral prefrontal cortex (O'Halloran et al, 2012). According to previous reports, cognitive impairments caused by a cerebellar lesion have been often explained by the functional suppression of the contralateral frontal lobe (Baillieux et al, 2006;Cooper et al, 2012;Lagarde, Hantkie, Hajjioui, & Yelnik, 2009;Mariën et al, 2008Mariën et al, , 1996Neau, Arroyo-Anllo, Bonnaud, Ingrand, & Gil, 2000;Peterburs, Bellebaum, Koch, Schwarz, & Daum, 2010;Suenaga et al, 2008).…”
mentioning
confidence: 97%
“…Some functional magnetic resonance imaging (MRI) studies revealed the cerebello-cortical pathway with multiple fiber tracts that terminate within the regions of the contralateral prefrontal cortex (O'Halloran et al, 2012). According to previous reports, cognitive impairments caused by a cerebellar lesion have been often explained by the functional suppression of the contralateral frontal lobe (Baillieux et al, 2006;Cooper et al, 2012;Lagarde, Hantkie, Hajjioui, & Yelnik, 2009;Mariën et al, 2008Mariën et al, , 1996Neau, Arroyo-Anllo, Bonnaud, Ingrand, & Gil, 2000;Peterburs, Bellebaum, Koch, Schwarz, & Daum, 2010;Suenaga et al, 2008).…”
mentioning
confidence: 97%
“…Symptom-lesion mapping, neuroanatomical and functional neuroimaging studies provide further indications that the cerebellum is involved in cognitive functioning [17][18][19][20][21][22][23][24]. Some studies have even found connections between lesions of the posterior lateral cerebellar hemispheres and higher order cognitive problems, whereas injuries involving the vermis of the cerebellum are accompanied by dysregulation of affect [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that neurocognitive problems after acquired pediatric cerebellar lesions have been described, reports about the emergence of cerebellar cognitive affective syndrome in this population are scarce [28][29][30][31]. Nevertheless, many authors stress the importance of an intact cerebellum for the development of neuropsychological functions [24,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As consistently reflected by CCD, the distant metabolic impact of surgical damage to the cerebellum via the dentatorubrothalamic tract on the supratentorial brain regions crucially involved in language dynamics and behavioral and affective regulation was later confirmed in an adolescent patient as well as in a larger study of 5 children with PFS. 7,8 The authors infer from the correlation between PFS symptoms and perfusional changes within the frontal lobe regions that "mutism in PFS is probably a speech apraxia rather than a simple dysarthria, dysphasia, or other cerebellar speech disorder. "…”
mentioning
confidence: 99%